Presence of resveratrol in wild Arachis species adds new value to this overlooked genetic resource - Carvalho, Paula Andreá Sampaio de Vasconcelos [UNESP]; de Carvalho Moretzsohn, Márcio; Brasileiro, Ana Cristina Miranda; Guimarães, Patrícia Messenberg; da Silveira Agostini-Costa, Tânia; da Silva, Joseane Padilha; Gimenes, Marcos A. (Springer Nature, 2020)
Genus Arachis comprises 82 species distributed into nine taxonomic sections. Most Arachis species are wild and those from Arachis section have been evaluated for many traits, since they can be used in peanut breeding. Most of the remaining species have been neglected and understudied. Recently, resveratrol content and expression of a resveratrol synthase gene were analyzed in wild Arachis species. Our aim was to expand the knowledge about resveratrol in Arachis, analyzing species from five sections and evaluating the expression of a resveratrol synthase (RS) gene responsive to ultraviolet light (UV) along the time. In a first experiment, the resveratrol content after UV induction was analyzed on detached leaves of 12 species from five sections. Variation was observed among species and accessions of the same species. The highest contents were found in A. lignosa (843.9 μg/g) and A. triseminata (745.4 μg/g). In a second experiment, RS expression and resveratrol content in four species and one synthetic amphidiploid were analyzed at 0, 7, 15 and 24 h pos induction (hpi) with UV. In most genotypes, the highest RS expression level was at 0 hpi, whereas the highest resveratrol content was at 15 hpi. Our results suggested that resveratrol is ubiquitously present in the genus Arachis with different capacities of synthesis among species and accessions in response to ultraviolet treatment. Presence of resveratrol in wild Arachis species adds new value to these genetic resources.